Pół wieku języka narodowego w liturgii. Doświadczenie z Czech - Komarek, Karel (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
After the Second Vatican Council, national languages began to be used in the Catholic liturgy and it was necessary to prepare translations of liturgical books. On this occasion, in the Czech Republic, the translation of the Bible was also revised and a new hymnal was published. The translation of the missal, especially the speeches delivered by the priest and the faithful at every mass became a very urgent task. In this article, we deal with the linguistic side of these translations, mainly of the Czech Missal. The translation of liturgical texts into Czech is not literal, it does not copy the syntax of the Latin original, but it always preserves its meaning. A neutral literary Czech was deliberately chosen for the translation so that the language of the liturgy would not become obsolete. After several years of using the Czech Missal, some modifications were made. For example, masculine forms were replaced by neutral ones so that they could be recited by both men and women.